Negotiating domination and resistance: English language learners and Foucault's Care of the Self in the context of English-only education. Issue 4 (3rd July 2016) - Bondy, Jennifer M.
Abstract : This article explores the basis for resistance to the normalizing technologies associated with English-only legislation and resulting educational practices. The dominance of English-only education in US public schools has normalized English first language speakers and English language learning by appropriating the technology of language in order to become 'Americanized.' Because of the growing number of English language learners (ELL) in US public schools, it is important to understand how the normalizing educational practices and disciplinary power associated with English-only education also cultivate possibilities for resistance. I draw upon Foucault's analytic care of the self to explore the space of English-only education by asking: 'What alternatives to the normalization of ELL students might be mobilized for resistance?' This analysis suggests that to shift from a normalized 'American' identity requires questioning the racist and nativist discourse on English-only education, and focusing attention on contradictory and multilayered notions of 'American'. The article concludes with recommendations for teacher education on how to cultivate prospective teachers' resistance to English-only education.